2
$\begingroup$

$a$ and $b$ are both positive real numbers. I'm supposed to work backwards (i.e. start with what I'm trying to prove and change it until something is absolutely true, then start from what is absolutely true in my proof).

Here's my attempt:

$\frac{2ab}{a+b}\leq\sqrt {ab}$

$\frac{2a^2b^2}{(a+b)^2}\leq{ab}$

$\frac{2a^2b^2}{a^2+2ab+b^2} - ab \leq 0$

$\frac{2a^2b^2-ab(a^2+2ab+b^2)}{a^2+2ab+b^2}\leq 0$

$\frac{2a^2b^2-a^3b-2a^2b^2-ab^3}{a^2+2ab+b^2}\leq 0$

$\frac{-a^3b-ab^3}{a^2+2ab+b^2}\leq0$

Because $a$ and $b$ are positive, this guarantees the left side is negative, making the inequality true.

$\endgroup$
4
  • 1
    $\begingroup$ This cannon be correct since you have equality if $a=b$. $\endgroup$
    – A.S.
    Jan 31, 2016 at 5:48
  • $\begingroup$ It's mostly correct (except you should write it backwards and replace < with <=) but a little complicated. It is simpler to square each side, simplify by $ab$ and get rid of denominators $\endgroup$ Jan 31, 2016 at 5:49
  • $\begingroup$ I tried this approach and got 0 $<=$ $(a-b)^2$, which could be $0$ if $a$ and $b$ are equal, or positive in any other case, which makes the inequality true. Hopefully I did the math right. $\endgroup$
    – Chris
    Jan 31, 2016 at 6:03
  • $\begingroup$ At the second step of your derivation, why didn't you square the $2$? $\endgroup$ Feb 18, 2021 at 9:42

3 Answers 3

6
$\begingroup$

This is just a rearrangement of the famous AM-GM inequality!

It states that $\frac{a+b}{2} \geq \sqrt{ab}$

for $a,b \geq 0$.

enter image description here

The proof is clear from the picture!

Now multiply by $\sqrt{ab}$ on both sides and rearrange with ease to get the desired: $\frac{2ab}{a+b}\leq\sqrt {ab}$.

$\endgroup$
0
$\begingroup$

Let $a,b\in\mathbb{R}$ with $a,b>0$.

$$\begin{align*}\frac{2ab}{a+b}\leq \sqrt{ab}&\Longleftrightarrow \frac{2}{a+b}\leq\frac{\sqrt{ab}}{ab}\\&\Longleftrightarrow \frac{2}{a+b}\leq\frac{1}{\sqrt{ab}}\\&\Longleftrightarrow\sqrt{ab}\leq\frac{a+b}{2}\\&\Longleftrightarrow 2\sqrt{ab}\leq a+b\\&\Longleftrightarrow 0\leq a-2\sqrt{ab}+b\\&\Longleftrightarrow 0\leq (\sqrt{a}-\sqrt{b})^2\end{align*}$$ where the last inequality is always true.

$\endgroup$
-1
$\begingroup$

A much simpler way is to use the relation between the harmonic and geometric means: $$ \frac{2}{\frac{1}{a}+\frac{1}{b}} \leq \sqrt{ab}$$ adding the fraction in the denominator of the left hand side: we have: $$ \frac{2}{\frac{b}{ab}+\frac{a}{ab}} \leq \sqrt{ab}$$ And the relation you listed follows.

See also https://en.wikipedia.org/wiki/Mean#Relationship_between_AM.2C_GM.2C_and_HM

$\endgroup$

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .